Estudio de prefactibilidad para la instalación de un centro de terapia física y rehabilitación para deportistas de alto rendimiento en Lima Metropolitana - Marcilla Angulo, Brenda (2023)
The present research work aims to demonstrate the technical, economic and social feasibility in the implementation of a rehabilitation and physical therapy center for athletes who maintain high performance in their performance. In the first chapter, the general aspects of the research are presented. In the second chapter, the market study will be developed to identify to which audience the service will be directed. In the third chapter, the micro location of the service will be determined. Additionally, the next chapter will identify the sizing of the service based on the factors of relationship between market size, resources, technology, investment and the break-even point. In the fifth chapter, topics related to the engineering of the project will be discussed. Additionally, the next chapter will determine how the organizational structure of the company will be. In the last two chapters, the total investment will be presented including the costs of service operations, income and expenditure budgets, financial budgets and financial and economic cash flows. At the end of this chapter, an analysis of the most representative economic indicators will be carried out. Finally, in the last chapter a social evaluation of the project will be determined in order to generate benefits to society.